Modern approaches to psychoterapy of somatoform disorders - Alsu I. Mukhametova; Valeriy V. Vasilyev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The scientific review focuses on the relevant for modern medicine problem of psychotherapy of somatoform disorders (SFD). It is based on the analysis of 106 publications on this topic (46 of them in Russian and 60 in English). The search for publications was carried out in the RSCI and Medline bibliographic databases. The purpose of the review was to form ideas about the current state of the psychotherapy of SFD with the highlighting and comparison of the main current approaches in this area. The review analyzes the overall effectiveness of psychotherapy of SFD and considers the following modern its directions: cognitive behavioral therapy, mindfulness-based psychotherapy, dynamic psychotherapy, group psychotherapy, other (rarely mentioned) psychotherapeutic methods, as well as polymodal and remote approaches to psychotherapy of SFD.The summary of the literary information presented in the review allows to conclude that psychotherapy today is considered by most authors as an important, possibly even leading component of the treatment of the considered mental pathology type. At the same time, data on its clinical effectiveness, especially in isolated use, remains ambiguous, in addition, among researchers there is still no unity of views on the main targets of psychotherapeutic impacts in SFD, as well as on the most suitable forms and methods of psychotherapy for the treatment of this pathology. Information on the clinical effectiveness of specific psychotherapeutic methods currently used for the treatment of SFD is either ambiguous or incomplete, and the polymodal approaches to psychotherapy of SFD proposed by some authors have insufficient scientific justification for the methodological combinations used in them. The future of psychotherapy of SFD is seen by the authors of this review in the development of integrative psychotherapeutic programs that combine elements of several multidirectional methods of psychotherapy, but that are based on knowledge of the general personal and psychological characteristics of patients suffering from SFD.